The assimilation of statistical techniques in the training of professionals in physical culture and sports /La asimilación de técnicas estadísticas en la formación del profesional en cultura física y deporte - Taimi Castañeda Rodríguez; Abelardo López Domínguez; Ana María Morales Ferrer; Victoria Del Carmen Collazo Frías (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The assimilation of statistical techniques is of great importance during the training of Physical Culture and Sports professionals, given the need for their application in scientific research work from the four graduate profiles and across all disciplines of the career. The implementation of learning strategies as tools for their assimilation, represents numerous benefits by virtue of training competent professionals. The diagnosis made to 107 students of the dau course and seven professors of the Computer Science and Data Analysis subject at the Manuel Fajardo University of Physical Culture and Sports Sciences allowed to detect, in the students, insufficiencies in the assimilation of these techniques, which prevents their correct application. Teachers show lack of mastery over learning strategies as tools that enhance self-learning and self-regulation. The objective of the study is to: design a didactic strategy that contributes to the assimilation of statistical techniques in the training of Physical Culture and Sports professionals. Among the methods used are analytical-synthetic, modeling, functional structural systemic, surveys and empirical frequency distribution tables. The theoretical assessment of the proposal, declared by the specialists in the ATJ Matrices, allowed to predict, with satisfactory criteria, the validity of the didactic strategy presented for its subsequent implementation.